Determining the Burden of Dysmenorrhea on Women’s Quality of Life: The Dysmenorrhea Symptom Interference Scale - Jahangeer, Syed Muhammad Ashraf; Fatima, Meerab; Iqbal, Hifza; Sheikh, Areeba (Gynecology Obstetrics & Reproductive Medicine, 2024)
OBJECTIVE: Dysmenorrhea negatively impacts a woman’s quality of life. The lack of proper awareness results in poor coping mechanisms in females. This study aims to determine the association of dysmenorrhea with quality of life using the Dysmenorrhea Symptom Interference (DSI) Scale and the management choices of females. STUDY DESIGN: This cross-sectional study was conducted among females studying at various universities in Karachi from March 2023 to May 2023. The calculated sample size was 270. A non-probability, convenience sampling technique was applied. A web-based, structured, self-administered questionnaire was used to collect data. RESULTS: 278 females completed the survey. The Numeric Rating Scale (NRS) score (1–10) indicated the degree of dysmenorrhea. The majority of the females, 40.6% (n=113), had moderate dysmenorrhea. Quality of life was measured according to the DSI Score (maximum score=5). The mean DSI score recorded was 2.75. Most participants (27%; n=75) were found in the mood component of DSI. Most of the females used lifestyle modifications, followed by home remedies and medications. A significant positive correlation between the NRS score and the DSI score (p<0.001) suggests that an increased degree of dysmenorrhea led to a significant decline in the quality of life. CONCLUSION: We conclude that dysmenorrhea is associated with a decreased quality of life and the DSI Scale is a valid tool for assessing its impact on quality of life. There is a general lack of knowledge about adequate pain management.